2020
DOI: 10.1007/s10803-020-04432-4
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Reactivity at 1 and 2 Years Old is Associated with ASD Severity During the Preschool Years

Abstract: Children with Autism Spectrum Disorder (ASD) often display atypical sensory reactivity within the first years of life, prior to a diagnosis. This study examined sensory reactivity patterns at 14 months, changes from 14 to 23 months, and later ASD severity at 3 to 5 years of age in children (n=87) at elevated likelihood of ASD. Results indicated that observed hyporeactivity at 14 months and increases from 14 to 23 months were related to higher ASD severity during the preschool Terms of use and reuse: academic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Findings from empirical research lend some support to this theory. Atypical patterns of sensory responsiveness, for example, have been linked to the core features of RRBs [ 6 , 11 , 12 , 13 , 14 , 15 ] and social communication in persons on the autism spectrum [ 12 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from empirical research lend some support to this theory. Atypical patterns of sensory responsiveness, for example, have been linked to the core features of RRBs [ 6 , 11 , 12 , 13 , 14 , 15 ] and social communication in persons on the autism spectrum [ 12 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…But additionally, a significant fraction of ASD patients also show abnormal reactions to environmental stimuli such as somatosensory input (Tomchek and Dunn, 2007). In fact, hyper-or hyporeactivity to different stimuli can act as predictor for diagnosis and/or severity of ASD (Grzadzinski et al, 2020;Jussila et al, 2020). The social impairment may in part be due to this altered perception of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory symptoms in the areas of hearing, vision, smell, and touch are prevalent in ASD patients, and can even appear during infancy. 20 21 Atypical sensory features may have detrimental cascading effects on social communication and reactivity, 21 and it was reported that sensory symptoms, such as reactivity, at 1 and 2 years of age are associated with ASD severity among preschool children. 20 Although we used simple hearing screening questions instead of a comprehensive evaluation of hearing, we found consistently increased risks of mortality for negative response to the question related to hearing impairment.…”
Section: Discussionmentioning
confidence: 99%